Learning from ERP implementation: A case study of issues and challenges in technology management - Nordin, Norani; Adegoke, Ojeniyi (Penerbit UTM Press, 2015)
Purpose: ERP implementation comes with huge business competitive advantages nevertheless it also has its difficulties and challenges.This paper presents the findings of field work and interview conducted on issues and challenges of ERP implementation on small and medium enterprises (SMEs).It proposes implementation strategies at each of the implementation stages for a successful ERP implementation within SMEs. Design/methodology/approach: The study employed both personal interview and observation methods. Findings: The findings revealed that reengineering (organization and infrastructures), top management commitment, funds, skilled manpower, implementation time and data fill-in were the critical issues and challenges faced by SMEs during ERP implementation.Hence, these factors were identifies as ERP implementation successful factors to be considered by SMEs.Also the study proposed three implementation strategies stages which will enhance successful ERP implementation in the SMEs.Originality/value: This study identified funds, skilled manpower and data fill-in as part of critical factors for successful ERP implementation in SMEs.Therefore, the study was used to generate successful implementation strategies for SMEs.